Trace element mapping by LA-ICP-MS: assessing geochemical mobility in garnet - Raimondo, T.; Payne, J.; Wade, B.; Lanari, P.; Clark, Christopher; Hand, M. (Springer, 2017)
© 2017, Springer-Verlag Berlin Heidelberg.A persistent problem in the study of garnet geochemistry is that the consideration of major elements alone excludes a wealth of information preserved by trace elements, particularly the rare-earth elements (REEs). This is despite the fact that trace elements are generally less vulnerable to diffusive resetting, and are sensitive to a broader spectrum of geochemical interactions involving the entire mineral assemblage, including the growth and/or dissolution of accessory minerals. We outline a technique for the routine acquisition of high-resolution 2D trace element maps by LA-ICP-MS, and introduce an extension of the software package XMapTools for rapid processing of LA-ICP-MS data to visualise and interpret compositional zoning patterns. These methods form the basis for investigating the mechanisms controlling geochemical mobility in garnet, which are argued to be largely dependent on the interplay between element fractionation, mineral reactions and partitioning, and the length scales of intergranular transport. Samples from the Peaked Hill shear zone, Reynolds Range, central Australia, exhibit contrasting trace element distributions that can be linked to a detailed sequence of growth and dissolution events. Trace element mapping is thus employed to place garnet evolution in a specific paragenetic context and derive absolute age information by integration with existing U–Pb monazite and Sm–Nd garnet geochronology. Ultimately, the remarkable preservation of original growth zoning and its subtle modification by subsequent re-equilibration is used to ‘see through’ multiple superimposed events, thereby revealing a previously obscure petrological and temporal record of metamorphism, metasomatism, and deformation.